2000
DOI: 10.1006/gcen.2000.7536
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of High-Affinity, Low-Capacity Estradiol-17β Binding in Rainbow Trout Scale Indicates a Possible Endocrine Route for the Regulation of Scale Resorption

Abstract: High-affinity, low-capacity estradiol-17␤ (Etestosterone, but not by diethylstilbestrol. Hence, the ligand binding specificity is different from that of the previously characterized liver E 2 receptor, where E 2 is displaced by diethylstilbestrol, but not by testosterone. The putative scale E 2 receptor thus appears to bind both E 2 and testosterone, and it is proposed that the increased scale resorption observed during sexual maturation in both sexes of several salmonid species may be mediated by this recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…The hypothesis of a direct effect of oestrogen on bone and/or scale remodelling in salmonids is supported by detection of oestrogen receptor (ER ) mRNA expression in these tissues in the trout (Armour et al 1997). Also, Persson et al (2000) recently characterised a high-affinity, low-capacity binding of E 2 to trout scales. In the sea bream, ER mRNA is not detected in bone and ER is expressed at low levels (only detectable by RT-PCR; Socorro et al 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis of a direct effect of oestrogen on bone and/or scale remodelling in salmonids is supported by detection of oestrogen receptor (ER ) mRNA expression in these tissues in the trout (Armour et al 1997). Also, Persson et al (2000) recently characterised a high-affinity, low-capacity binding of E 2 to trout scales. In the sea bream, ER mRNA is not detected in bone and ER is expressed at low levels (only detectable by RT-PCR; Socorro et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In goldfish, killifish (Mugiya & Watabe 1977) and rainbow trout (Carragher & Sumpter 1991, Persson et al 1994, bone is initially spared and calcium mobilisation takes place predominantly from the scales. Moreover, in juvenile rainbow trout the effect of oestrogen at the level of the scales appears to be via high-affinity, low-capacity E 2 -binding sites (Persson et al 2000) and oestrogen receptor mRNA is expressed in this tissue (Armour et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Yamada et al (2002) found that during sexual maturation in female Japanese eels, the calcium and phosphorus contents of the skin (which contains the few scales) remained unchanged, while they decreased in the vertebral skeleton, which constitutes the principal source for calcium and phosphorus. Estrogen receptors were reported in bone and scales of rainbow trout (Armour et al 1997, Persson et al 2000, regenerating scales of goldfish (Yoshikubo et al 2005) and bone of sea bream (Socorro et al 2000). This suggests a possible direct effect of E 2 on bone and scale demineralization in teleosts, related to the strong demand in minerals for Vg production in oviparous vertebrates.…”
Section: E 2 Action On Bone Demineralization: An Oviparous Featurementioning
confidence: 93%
“…E 2 -specific binding [17] was detected in the scales of rainbow trout. However, a different action from E 2 -treated scales was obtained in OHPAH- scales.…”
Section: Discussionmentioning
confidence: 93%